Beyond al-Qaeda: Part 1, The Global Jihadist Movement - Rabasa, Angel; Chalk, Peter; Cragin, Kim; Daly, Sara A.; Gregg, Heather S. (RAND Corporation, 2023)
Examines al-QaedaÂ•s evolution and the emergence of the broader global jihadist movement-groups affiliated, associated, or inspired by al-Qaeda-and the threat that they pose to the United States and U.S. allies and interests. The authors conclude by setting out a four-pronged strategy to counter the jihadist threat.